Dampak Undang-Undang Nomor 4 Tahun 2023 Tentang Pengembangan dan Penguatan Sektor Keuangan (P2SK) Terhadap Kelangsungan Dana Pensiun - Affandi, Muhammad Rispan; Harahap, Evi Syuriani (Journal Economy and Currency Study (JECS), 2024)
The purpose of this study was to determine the impact of Law No. 4 of 2023 concerning the development and strengthening of the financial sector (P2SK) on the continuity of pension funds. This research was conducted with a qualitative approach and is descriptive in nature with data collection tools, namely in-depth and staged interviews. The results obtained are Law No. 4 of 2023 is expected to increase the level of financial inclusion in the pension fund sector, increase old age protection for the community, especially workers, encourage public confidence in the implementation of pension programs and accelerate the accumulation of long-term funding sources as the main source of development financing.